Characterizing air-coupled gas discharge acoustic transducers by using scanning laser Doppler refracto-vibrometry; Optics and Lasers in Engineering; Vol. 175 - Derusova D. A. Dariya Aleksandrovna; Vavilov V. P. Vladimir Platonovich; Nekhoroshev V. O. Vitaly Olegovich; Shpilnoy V. Yu. Viktor Yurjevich (2024, 2024)
Title screen